Thermal decomposition behavior of ammonium perchlorate catalyzed by cobalt-based complexes - ZHOU Peng; ZHANG Siwei; REN Zhuoqun; TANG Xiaolin; ZHANG Kuan; ZHANG Yifu; HUANG Chi (Cailiao gongcheng)
The addition of a burning rate catalyst can affect the decomposition of oxidants and effectively regulate the burning rate of solid propellants. MOFs have aroused attentions due to their excellent properties in catalyzing the thermal decomposition of ammonium perchlorate （AP）， and existing research has mainly focused on changes in metal centers， without discussing the influence of ligands on the catalytic process. We prepare three types of Co-based complexes （Co-CP） catalysts using three different ligands （2-methylimidazole， terephthalic acid， and 1，2，4，5-phenylenetetramine） and discuss their effects on the thermal decomposition behavior of AP. The results indicate significant differences in the decomposition behavior of the three Co-CPs in AP due to differences in ligands. Co-ZIF can significantly reduce the decomposition temperature of AP while enhancing the heat release of the system. The relatively high thermal stability of Co-BDC affects the catalytic effect of AP thermal decomposition. Co-BTA can delay the low-temperature decomposition of AP by releasing NH3 through ligand decomposition. The gas-phase products during the reaction process are captured through thermogravimetric infrared spectroscopy （TG-IR） testing， and the possible mechanisms of AP decomposition catalyzed by different Co-CPs are further explored and discussed. This study provides a design approach for a metal complex-based combustion rate catalyst.